Material Stock and Flow Analysis within the Agricultural Building Sector Based on Local Database - Hancz, Gabriella; Kovács, József (International Journal of Engineering and Management Sciences, 2018)
The purpose of the paper is to analyze on micro level the stream of building materials needed for raising cattle. The scope of the produced material flow chart will cover the inflow and storage of the materials. The overall objective of material flow analysis is to contribute to the data inventory development process which is needed to use these construction materials as secondary raw materials in the future. The assessment is based on a concrete new development in a Hungarian region being carried out nowadays as a development and modernization of an existing cattle raising farm. Driven by the concern of resource depletion, further research on higher level, based on larger database will be needed to verify the estimated national level results for the magnitude of growth of anthropogenic stocks.